Mechanical thrombectomy and the 'weekend effect': does admission time influence outcomes?. (2020) - Weddell, Jake; Muddegowda, Girish; Natarajan, Indira; Nayak, Sanjeev; Jadun, Changez; Hashim, Zafar; Ferdinand, Phillip; Sanyal, Ranjan; Augustine, Albin; Roffe, Christine
No abstract available